Quality of health care: informatics foundations - Hasman, A.; Safran, C.; Takeda, H. (Yearbook of Medical Informatics, 2003)
In this article we will discuss in what ways computer systems can contribute to the quality of healthcare and on which principles of informatics successful systems are founded. Section 2 presents an overview of studies that investigate the usefulness of decision support, and Section 3 discusses factors that determine the success of decision support systems. The foundations of guideline systems are presented in Section 4. Section 5 offers a brief review of physician order entry, and Section 6 presents a discussion of medical risk management and the results of Japanese studies in this area.